PENGEMBANGAN POTENSI DESA WISATA BERBASIS BUDAYA TINJAUAN TERHADAP DESA WISATA DI JAWA TENGAH - Priyanto Priyanto (Program Pendidikan Vokasi Universitas Indonesia, 2016)
This study to unearth village tourism for culture attraction tourim and to show there are some basicproblem for existence village tourism in Central Jawa. The methodology was used qualitative researchmethod with descriptive analysis. The result of this stuy indicate that for general potential culturalvillage tourism in Central Java is many. The problems that for like human resource, infrastructure &facillity, promotion. The problems can be finish with active any other especialy the people from culturevillage tourism.Keywords: Village Tourism, Atraction Tourism, Culture Tourims